Trst, Bonomo in reformacija - Grdina, Igor (Slavia Centralis, 2020)
Trieste, Bonomo, and the ReformationPeter Bonomo (1458–1546) was a central figure of Trieste’s history. During his tenure as bishop, the town’s formerly strong pro-Venetian "party" was rendered insignificant and the pro-emperor stance gained importance. Its proponent, humanist Bonomo, viewed Trieste as an autonomous unit within the framework of the universal Habsburg Monarchy. Throughout, his efforts to link the town and its hinterlands were tied to advocating for its autonomous status. Such status was achieved around 1550.
Keywords: Peter Bonomo; Trieste; humanism; Habsburg court; Reformation